Self-defense mechanism of the main characters in the novel Pünktchen und Anton: A study of Sigmund Freud's psychoanalytic theory - Zahrah, Nada Muthia; Melky Ayu Wijayanti; Zuriyati; Siti Gomo Attas (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Self-defense mechanism is part of Sigmund Freud's psychoanalytic theory. According to Freud, self-defense mechanism is an individual way of coping with anxiety-related outbursts. Anxiety can arise when there is a conflict of desire between the id and ego because the id gets a sex drive and aggression that forces the ego to do something it wants. The problem of individuals who overcome anxiety by self-defense can also occur in human